Innovative cross-linked electrospun PVA/MOF nanocomposites for removal of cefixime antibiotic - Razieh Mirzaei; Shahram Tangestaninejad; Afsaneh Marandi; Majid Moghadam; Iraj Mohammadpoor-Baltork; Reihaneh Kardanpour; Hossein Abdolvand (Scientific Reports)
Abstract In this study, we synthesized two nanocomposites, cross-linked PVA/HKUST and PVA/ZIF-67, by integrating metal–organic frameworks (MOFs) into electrospun polyvinyl alcohol (PVA). Several characterization techniques including FTIR, XRD, ICP, SEM, TGA, UV–Vis, zeta potential, and N2 adsorption–desorption were employed. The adsorption performance of the composites for cefixime (CFX) removal was assessed under varying conditions such as MOF content, contact time, pH, initial CFX concentration, and temperature. ZIF-67 and HKUST contribute to the high adsorption efficiency of the composites by providing a porous structure with high surface area, facilitating interactions with CFX molecules, and enhancing the overall stability of the composite material in the removal process. The Langmuir isotherm model revealed a maximum adsorption capacity of 282.5 mg/g for PVA/HKUST and 211.4 mg/g for PVA/ZIF-67. Notably, CFX was rapidly removed within 50 min, demonstrating the high potential of these nanofibers in wastewater treatment. However, after six cycles, removal efficiencies declined from 88 to 74% for PVA/HKUST and from 85 to 59% for PVA/ZIF-67.